The Effect of Regular Congregational Prayer Practices on the Religious Attitudes of Students at SD Muhammadiyah 29 Surabaya. - Aishah Ayu Addawiyah; Khodijah Irbatur Robbaniyyah; Nur Alfiyah; Benny Prasetiya (Al-Hikmah: International Journal of Islamic Studies, 2026)
The formation of religious attitudes in elementary school ged children is a foundational aspect of personality development, cultivated through the habituation of regular worship practices within the school environment. This study aims to analyse the effect and the magnitude of the contribution of congregational prayer habits to the religious attitudes of students at SD Muhammadiyah 29 Surabaya. The research employed a quantitative associative causal approach with a population of 50 fifth  and sixth-grade students. Data were collected using closed-ended questionnaires that had been tested for validity and reliability, and subsequently analysed using simple linear regression through SPSS version 26. The results indicate that congregational prayer habits have a positive and significant effect on students’ religious attitudes, with a significance value of 0.000 (< 0.05). The coefficient of determination (R²) of 0.639 shows that congregational prayer habits contribute 63.9% to students’ religious attitudes, while the remaining percentage is influenced by other factors outside the scope of this study. These findings confirm that the consistent implementation of congregational prayer within the school environment is an effective strategy for fostering and strengthening the religious attitudes of elementary school students